2023
DOI: 10.3389/fendo.2023.1165415
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sucrose and arsenic on muscular insulin signaling pathways differ between the gastrocnemius and quadriceps muscles

Abstract: IntroductionInsulin resistance in muscle can originate from a sedentary lifestyle, hypercaloric diets, or exposure to endocrine-disrupting pollutants such as arsenic. In skeletal muscle, insulin stimulates glucose uptake by translocating GLUT4 to the sarcolemma. This study aimed to evaluate the alterations induced by sucrose and arsenic exposure in vivo on the pathways involved in insulinstimulated GLUT4 translocation in the quadriceps and gastrocnemius muscles.MethodsMale Wistar rats were treated with 20% suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…As-induced liver injury or dysfunction can impact these processes, leading to imbalances in glucose levels. 22,23 Besides, liver dysfunction caused by As exposure may exacerbate hepatic IR, leading to poor management of blood glucose levels 62,63 Serum ALT levels are commonly associated with liver fat, 64 and they may reflect an indirect marker of hepatic IR because an excess of fat accumulation in the liver induces liver IR. 65 This study demonstrated a greater portion of the mediating effect in nondrinkers than in the overall population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As-induced liver injury or dysfunction can impact these processes, leading to imbalances in glucose levels. 22,23 Besides, liver dysfunction caused by As exposure may exacerbate hepatic IR, leading to poor management of blood glucose levels 62,63 Serum ALT levels are commonly associated with liver fat, 64 and they may reflect an indirect marker of hepatic IR because an excess of fat accumulation in the liver induces liver IR. 65 This study demonstrated a greater portion of the mediating effect in nondrinkers than in the overall population.…”
Section: Discussionmentioning
confidence: 99%
“…It helps in the processes of gluconeogenesis and glycogenolysis, and it stores excess glucose as glycogen. As-induced liver injury or dysfunction can impact these processes, leading to imbalances in glucose levels. , Besides, liver dysfunction caused by As exposure may exacerbate hepatic IR, leading to poor management of blood glucose levels , Furthermore, the efficiency of As metabolism and detoxification may further decline because of the impaired liver tissue caused by chronic low As exposure. Serum ALT levels are commonly associated with liver fat, and they may reflect an indirect marker of hepatic IR because an excess of fat accumulation in the liver induces liver IR .…”
Section: Discussionmentioning
confidence: 99%